Mechanisation in tea plantation driving factors and its impact on sustainable environment - I Dewa Putu Eskasasnanda; Agung Wiradimadja (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2020)
Mechanization in tea plantation business is a phenomenon that is happening in Indonesia. The demand for tea products, the existence of land and tea plants that must be routinely maintained makes the managers of tea plantations have to find ways to manage tea plantations. Mechanization is a strategy taken by planters to cultivate land and maintain the amount of tea products when fewer workers are attracted to the tea plantation business. This paper will discuss the mechanization that occurs in the tea plantations of Serah Kencong, Blitar Regency. The focus of this paper is to explain the causes of mechanization in Serah kencong tea plantations, the views of tea pickers about the mechanization on these tea plantations, and the impact of mechanization on the lives of Serah Kencong planter communities and the natural environment.